Mathematical Modelling of the Internal and External Piping Configurations Effect on the Solar Thermal System - Rajab, Ghabour; Louay, Haikal (Journal of Central European Green Innovation, 2023)
Countless types of renewable energy can easily be exploited like wind, biomass, and solar. The most common power is solar power; it is usually used to get various outputs like electricity generation by photovoltaic/thermal power plants and local water heating. The task is to introduce environmentally friendly technologies, so the government authorities worldwide motivate the use of solar domestic water heating for its primary usage, low upkeep requirements, and the efficiency of the solar heating systems. Domestic solar hot water units, if effectively designed, are competent in providing most hot water demands in an appropriate environment and cost-effective approach. Despite 50 years of development, business technology has certainly not yet achieved substantive market penetration instead of mainstream electric power and gas alternatives. Various stakeholders will consider solar power heating systems utilised in buildings as an attractive alternative to traditional space and water heating methods. However, their functionality depends on climatic conditions, typical water heating requirements, and even operational parameters that could provide chances for performance optimisation. This study aims to analyse the effect of piping parameters on the solar system in the city of Budapest, Hungary using two programs, T*SOL as a solar system simulator and R-Studio as coding software. The analysis uses the simple model of the solar water heating system considering the following factors (pipe diameters, internal length, external length, Glycol, Thickness, volume flow rate, insulation), aiming to study the effect of the internal and external piping system. The study is carried out by simultaneously changing the values of the variables mentioned above by applying linear modelling and changing the collector type to choose the most appropriate system from the solar fraction aspect.